Download presentation

Presentation is loading. Please wait.

Published byAudrey Keating Modified over 3 years ago

1
4 minutes Warm-Up Solve each equation for x. Round your answers to the nearest hundredth. 1) 10x = 1.498 2) 10x = Find the value of x in each equation. 3) x = log4 1 4) ½ = log9 x

2
**6.4.1 Properties of Logarithmic Functions**

Objectives: Simplify and evaluate expressions involving logarithms Solve equations involving logarithms

3
**Properties of Logarithms**

For m > 0, n > 0, b > 0, and b 1: Product Property logb (mn) = logb m + logb n

4
**Example 1 given: log5 12 1.5440 log5 10 1.4307 log5 120 =**

5
**Properties of Logarithms**

For m > 0, n > 0, b > 0, and b 1: Quotient Property logb = logb m – logb n m n

6
**Example 2 given: log5 12 1.5440 log5 10 1.4307 12 log5 1.2 = log5**

–

7
**Properties of Logarithms**

For m > 0, n > 0, b > 0, and any real number p: Power Property logb mp = p logb m

8
**Example 3 given: log5 12 1.5440 log5 10 1.4307 log5 1254**

53 = 125 = 4 3 x = 3 = 12

9
**Practice Write each expression as a single logarithm.**

1) log2 14 – log2 7 2) log3 x + log3 4 – log3 2 3) 7 log3 y – 4 log3 x

10
Homework p.382 #13-21 odds,31,35

11
4 minutes Warm-Up Write each expression as a single logarithm. Then simplify, if possible. 1) log6 6 + log6 30 – log6 5 2) log6 5x + 3(log6 x – log6 y)

12
**6.4.2 Properties of Logarithmic Functions**

Objectives: Simplify and evaluate expressions involving logarithms Solve equations involving logarithms

13
**Properties of Logarithms**

For b > 0 and b 1: Exponential-Logarithmic Inverse Property logb bx = x and b logbx = x for x > 0

14
Example 1 Evaluate each expression. a) b)

15
**Practice Evaluate each expression. 1) 7log711 – log3 81**

16
**Properties of Logarithms**

For b > 0 and b 1: One-to-One Property of Logarithms If logb x = logb y, then x = y

17
**Example 2 Solve log2(2x2 + 8x – 11) = log2(2x + 9) for x.**

2x2 + 8x – 11 = 2x + 9 2x2 + 6x – 20 = 0 2(x2 + 3x – 10) = 0 2(x – 2)(x + 5) = 0 x = -5,2 Check: log2(2x2 + 8x – 11) = log2(2x + 9) log2 (–1) = log2 (-1) undefined log2 13 = log2 13 true

18
**Practice Solve for x. 1) log5 (3x2 – 1) = log5 2x**

2) logb (x2 – 2) + 2 logb 6 = logb 6x

19
Homework p.382 #29,33,37,43,47,49,51,57,59,61

Similar presentations

© 2017 SlidePlayer.com Inc.

All rights reserved.

Ads by Google